Amphiregulin Regulates Phagocytosis-Induced Cell Death in Monocytes via EGFR and the Bcl-2 Protein Family. (3rd November 2019) - Platen, Christopher; Dreschers, Stephan; Wappler, Jessica; Ludwig, Andreas; Düsterhöft, Stefan; Reiss, Lucy Kathleen; Orlikowsky, Thorsten W.
Abstract : Neonates are extremely susceptible to bacterial infections, and evidences suggest that phagocytosis-induced cell death (PICD) is less frequently triggered in neonatal monocytes than in monocytes from adult donors. An insufficient termination of the inflammatory response, leading to a prolonged survival of neonatal monocytes with ongoing proinflammatory cytokine release, could be associated with the progression of various inflammatory diseases in neonates. Our previous data indicate that amphiregulin (AREG) is increasingly expressed on the cell surface of neonatal monocytes, resulting in remarkably higher soluble AREG levels after proteolytic shedding. In this study, we found that E. coli -infected neonatal monocytes show an increased phosphorylation of ERK, increased expression of Bcl-2 and Bcl-XL, and reduced levels of cleaved caspase-3 and caspase-9 compared to adult monocytes. In both cell types, additional stimulation with soluble AREG further increased ERK activation and expression of Bcl-2 and Bcl-XL and reduced levels of cleaved caspase-3 and caspase-9 in an EGFR-dependent manner. These data suggest that reduced PICD of neonatal monocytes could be due to reduced intrinsic apoptosis and that AREG can promote protection against PICD. This reduction of the intrinsic apoptosis pathway in neonatal monocytes could be relevant for severely prolonged inflammatory responses of neonates.